Resenha - Barbosa, Jorge Luiz (Cadernos do Desenvolvimento Fluminense, 2013)
<doi>10.12957/cdf.2013.9097 ELIANA SOUSA e SILVA. Testemunhos da Maré. Rio de Janeiro: Coleção Tramas Urbanas Aeroplano, 2012. 296p.